“When the Cock crows, the Devil Falls” – a Review of Christian Thought Concerning Birds in Selected Folk Tales - Tańczuk, Agnieszka (Studia Ecologiae et Bioethicae, 2021)
In the consumptive world, mysterious things function as magic or superstition, sometimes via tradition, or a relic of a by-gone era. However, we are still afraid to see a black cat, and somebody remembers the celandine (in Polish “jaskółcze ziele”), though nobody knows its connotation with the swallow. The image of birds in folk tales connects the observation of nature, throughout the year and religious holidays, with their consequences for Man. Since the beginning, Man has admired nature, being afraid of its wildness and primeval power. When one joined it with divinity, it aroused fear even more, but also evoked greater fascination. In this article, I present the essence of myths in folk stories, and its function on the example of birds which have lived in proverbs and sayings. I will also show the variety of references to the cult of Christian saints, the love of the land, and the nature that surrounds us. I would like to show how our attitude towards nature has changed, and what is the function of birds as an element of the environment. I would also like to answer the question; does a modern man need myths to discover his sense of life and realise its meaning?